Nanoporous covalent organic framework embedded with Fe/Fe3O4 nanoparticles as air-stable low-density nanomagnets - Kushwaha, Rinku; Kaleeswaran, Dhananjayan; Haldar, Sattwick; Chakraborty, Debanjan; Mullangi, Dinesh; Borah, Aditya; Vinod, Chathakudath P.; Murugavel, Ramaswamy; Vaidhyanathan, Ramanathan (ACS Applied Nano Materials, 2020)
Covalent organic frameworks (COFs) made of light atoms such as H, C, N, and O with a significant void-to-framework ratio are excellent low-density supports for nanoparticles (nPs). Their framework can be precoded with heteroatoms to ensure binding with metallic nanoclusters. With these advantages, if controlled amounts of magnetic nPs are anchored to them, they can yield low-density organic-inorganic nanomagnets. Their organic nature facilitates fusion with bulk materials such as paper/textile to enable bulk composites with well-dispersed low-density magnets, which have potential for defense and next-generation aviation applications. Herein, we have grown small Fe/Fe3O4 nPs (5-18 wt %) inside a COF. Interestingly, 300 mg of this organic-inorganic framework material (containing 50 mg of nPs) can lift a vial of similar to 15,000 mg (300 times heavier). Also, the hydrophobic COF wraps around the Fe/Fe3O4 nanocluster retaining its room-temperature magnetic character even after 1 year, while the naked nPs lose it within a few days because of air oxidation. Bulk composites with paper and polymers have been made using this low-density Fe-COF to demonstrate their processability.
Keywords: air-stable nanomagnets; Covalent organic framework; Fe/Fe3O4 nanoparticles; low-density nanomagnets; magnetic rayon; nanoporous COF

Noble-metal-free heterojunction photocatalyst for selective CO2 reduction to methane upon induced strain relaxation - Das, Risov; Sarkar, Shreya; Kumar, Ritesh; Ramarao, Seethiraju D.; Cherevotan, Arjun; Jasil, Mohammed; Vinod, Chathakudath P.; Singh, Abhishek Kumar; Peter, Sebastian C. (ACS Catalysis, 2022)
Sunlight-driven CO2 hydrogenation has drawn tremendous attention. However, selective CH4 formation via CO2 photoreduction is very challenging. Herein, we report a metal oxide semiconductor heterojunction consisting of BiVO4 and WO3 as a photocatalyst for the efficient conversion of carbon dioxide (CO2) selectively to methane (105 mu mol g(-1) h(-1)) under visible light in the absence of a sacrificial agent. Wise selection of the reaction medium and the strategically tuned heterojunction upon strain relaxation suppresses the competitive hydrogen generation reaction. The detailed photophysical, photoelectrochemical, and X-ray absorption spectroscopy studies pointed to the Z-scheme mechanism of electron transfer, which favors superior electron and hole separation compared to the individual components of the composite catalyst and other well-known photocatalysts reported for CO2 reduction. The observations are further corroborated by experimental diffuse reflectance infrared Fourier transform spectroscopy and theoretical density-functional theory calculations, which reveal that the heterojunction has a lower free-energy barrier for CO2 conversion to CH4 due to the larger stabilization of the *CH2O intermediate on the strain-relaxed heterojunction surface, in comparison to the pristine BiVO4 surface. The present work provides fundamental insights for constructing high-performance heterojunction photocatalysts for the selective conversion of CO2 to desired chemicals and fuels.
Keywords: CO2 reduction; heterostructure; methane; Photocatalysis; Z-scheme